An unplugged remix of culturally responsive computing for early childhood education - Frances K. Harper; James A. Larsen; Margaret Quinn; Lori Caudle; Bethany Parker; Amir Sadovnik; The CRRAFT Partnership (Future in Educational Research)
Abstract Despite a growing movement towards expanding computer science education in PreK‐12, gaps in computing opportunities along lines of race, ethnicity, class, and gender have widened. Emergent theories and practices related to culturally responsive computing show promise in addressing this gap; however, little is known about engaging Black, Latinx, and Indigenous preschoolers in computer science. In this paper, we utilized qualitative content analyses to explore how an early childhood computer science curriculum created opportunities for young Black and Latinx preschoolers to develop computational thinking skills while engaging in culturally responsive computing. Overwhelmingly, we found the curriculum, co‐developed with educators and caregivers, emphasized unplugged tools and coding activities to support computational thinking. These unplugged opportunities positioned children as innovators with technology and technosocial change agents, in developmentally‐appropriate, play‐based ways. Findings demonstrate a need to emphasize the value of unplugged tools and coding activities in order to support computational thinking and align the goals of culturally responsive computing with the unique needs of young children. We discuss implications for a theory of culturally responsive computing specifically for early childhood education.